Frequency of Newly Diagnosed Diabetes Mellitus in Acute Ischemic Stroke Patients - Mohammad Hashim; Khan, Atta Muhammad; Ahmad, Izaz; Muhammad Yaseen; Khalil, Asad; Muhammad, Sohail; Arif Ullah (Indus Journal of Bioscience Research, 2025)
Background: Diabetes mellitus is a major risk factor for ischemic stroke and is often undiagnosed until complications arise. Early identification of previously unrecognized diabetes in stroke patients is essential for improving clinical outcomes and preventing recurrence. Objective: To determine the frequency of newly diagnosed diabetes mellitus in patients presenting with acute ischemic stroke. Methodology: The study was a cross-sectional research undertaken in the Department of Medicine, Lady Reading Hospital, Peshawar in July 22, 2024-January 22, 2025. Non-probability consecutive sampling was used to enroll 150 patients with the established acute ischemic stroke. Patients who had a history of diabetes were not included. Fasting blood glucose levels and HbA1c levels were measured and blood samples were collected. New diagnosis of diabetes mellitus was fasting plasma glucose 126mg/dL or HbA1c 6.5%. Data analysis was done through the SPSS version 26. Results: The mean age of patients was 61.4 ± 11.2 years, with 61.3% males and 38.7% females. Also, 46 (30.7) patients and 104 (69.3) patients were non-diabetic and newly diagnosed with diabetes mellitus, respectively. Males and patients aged ≥60 years had a higher rate; but the relationships were not statistically significant. Conclusion: Acute ischemic stroke patients with pre-existing diabetes mellitus is found in a significant population. Regular examination of diabetes amongst stroke patients is highly encouraged to enhance correct diagnosis, proper management, and better clinical results